Study on the interactions between melamine-cored Schiff bases with cucurbit[n]urils of different sizes and its application in detecting silver ions - Gou, Jun-Xian; Luo, Yang; Yang, Xi-Nan; Zhang, Wei; Lu, Ji-Hong; Tao, Zhu; Xiao, Xin (Beilstein Journal of Organic Chemistry, 2021)
Three different complexes, TMeQ[6]-TBT, Q[7]-TBT, and Q[8]-TBT are constructed by three different cucurbiturils and synthesized by guest melamine-cored Schiff bases (TBT) through outer-surface interaction and host–guest interactions. TBT forms a TMeQ[6]-TBT complex with TMeQ[6] through outer-surface interaction, while Q[7]-TBT and Q[8]-TBT form complexes with Q[7,8] through host–guest interactions. Among them, Q[7]-TBT is selected as a UV detector for the detection of silver ions (Ag+). This work makes full use of the characteristics of each cucurbituril and melamine-cored Schiff base to construct a series of complexes and these are applied to metal detection.
Keywords: cucurbiturils; melamine; Schiff base; silver ion